ANALISIS KETERAMPILAN METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH SPLDV DI SMP NEGERI 4 MALANG - Nurul Ma’rifah; Akbar Sutawidjaja; I Made Sulandra (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
This qualitative descriptive study aims to describe the metacognitive skills of 3 class VIIIA students of SMP Negeri 4 Malang in solving mathematical problems related to the Two Variable Linear Equation System (SPLDV). The three subjects respectively had high, medium and low abilities based on the initial test of SPLDV. Data were collected through written tests, metacognitive skills self-assessment questionnaires, and interviews. The data were analyzed using three components of metacognitive skills, namely planning, monitoring and evaluation skills. The results showed that subjects with high and moderate abilities met the indicators of planning skills A1, A2 and A3, while subjects with low abilities met the indicators of planning skills A3. The monitoring skills of subjects with high and low abilities meet two indicators B1 and B2, while subjects with moderate abilities only meet one indicator, namely B1. In the evaluation skills of the three research subjects only met one indicator, namely C1.